A rare case of orthostatic headache due to spontaneous intracranial hypotension. Issue 2 (28th December 2015) - Arshed, Sabrina; Enakuaa, Souad; Nai, Qiang; Hossain, Mohammad Amir; Tulpule, Sunil; Yousif, Abdalla
Key Clinical Message: Headache is one of the most common clinical entities, and has a long list of differential diagnoses; however, one of the more uncommon causes of postural headache is spontaneous intracranial hypotension. It is important that clinicians be aware of this condition, as it is often overlooked, leading to invasive and unnecessary diagnostic testing. A good history and physical exam, paired with an MRI of the brain is sufficient to make the diagnosis of SIH, relieve the symptomology of the patient in a quick and efficient manner, and avoid costly invasive procedures. Abstract : Headache is one of the most common clinical entities, and has a long list of differential diagnoses; however, one of the more uncommon causes of postural headache is spontaneous intracranial hypotension. It is important that clinicians be aware of this condition, as it is often overlooked, leading to invasive and unnecessary diagnostic testing. A good history and physical exam, paired with an MRI of the brain is sufficient to make the diagnosis of SIH, relieve the symptomology of the patient in a quick and efficient manner, and avoid costly invasive procedures.